A Prospective Ultrasound Study of Prenatal Growth in Infant Siblings of Children With Autism. Issue 2 (7th July 2015) - Unwin, Lisa M.; Maybery, Murray T.; Murphy, Anthony; Lilje, Wendy; Bellesini, Michelle; Hunt, Anna M.; Granich, Joanna; Jacoby, Peter; Dissanayake, Cheryl; Pennell, Craig E.; Hickey, Martha; Whitehouse, Andrew J.O.
Abstract : Numerous studies have observed that a proportion of infants later diagnosed with autism spectrum disorder (ASD) experience accelerated head growth during the first years of life. An emerging methodology for examining the developmental trajectory prior to a diagnosis of ASD is to investigate siblings of affected individuals. The current study is the first prospective investigation of fetal growth in siblings of children with ASD. Two groups of pregnant women were recruited as part of the PRegnancy Investigation of Siblings and Mothers of children with autism cohort in Perth, Western Australia. The "high risk" group ( n  = 23) comprised pregnant women who have an existing child with a diagnosis of ASD and the "low risk" group ( n  = 36) comprised pregnant mothers who have an existing child who has developed typically. Prenatal ultrasounds were procured at multiple time‐points throughout the second‐ and third‐trimesters, enabling an examination of growth trajectories. Growth measurements were then compared for the high‐ and low‐risk fetuses. Mixed linear regression models identified no significant differences between the high‐ and low‐risk fetuses in the rate of prenatal head and body growth throughout the second‐ and third‐trimester (all P‐ values >0.05). Similarly, there were no significant differences observed when comparing high and low risk groups on a ratio of head circumference relative to body size ( β  = −0.019, P = 0.75). Future studies may consider looking beyond the macro architecture of the prenatal brain and examine the growth of brain subregions that have been implicated in the presentation of ASD symptoms. Autism Res 2016, 9: 210–216 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.